Primary osteosarcoma of frontal bone: A case report and review of literature. Issue 51 (December 2017) - Wu, Guangyong; Liang, Qi; Liu, Yu
Abstract: Rationale: Primary osteosarcomas of the skull and skull base are rare, comprising <2% of all skull tumors. Primary osteosarcomas of the skull are aggressive neoplasms composed of spindle cells producing osteoid which have poor outcome. Patient concerns: A 33-year-old woman was admitted to our hospital with a major complaint of a growing mass on her left frontal region of the skull for 10 months. Prior to the accurate diagnosis, the mass on her skull was considered to be eosinophilic granuloma. Diagnoses: Computerized tomogram (CT) scan of skull revealed a lytic lesion causing destruction of left frontal bone with surrounding soft tissue mass. The histological examination of the lesion showed typical features of osteosarcoma. Interventions: The patient received 3 surgeries and adjuvant chemotherapy and radiotherapy for the frontal bone lesion. Outcomes: At the last follow-up, after 4 years, the patient was free of disease both clinically and on imaging by magnetic resonance imaging (MRI) scan after 4 years. Lessons: Because osteosarcoma of skull is a rare disease, the early recognition and correct diagnosis are very important for a better prognosis. It is therefore imperative that clinicians recognize osteosarcoma early to make an accurate diagnosis and complete surgical resection followed by combined chemo-radiation is proved to be one of the most optimal treatment regimens.